Microbial succession in human rib skeletal remains and fly-human microbial transfer during decomposition - Deel, Heather Leigh, author; Metcalf, Jessica L., advisor; Wilusz, Carol, committee member; Trivedi, Pankaj, committee member; Pante, Michael, committee member (Colorado State University. Libraries, 2022)
Human decomposition is a dynamic process partially driven by the actions of microbes. It can be defined by the fresh, early decomposition, advanced decomposition, and skeletonization stages. The microbial communities that facilitate decomposition change in a predictable, clock-like manner, which can be used as a forensic tool for estimating postmortem interval. Chapter 1 introduces this concept by describing the stages of decomposition in detail and how high-throughput sequencing methods can be used with microbes to develop models for predicting postmortem interval. Chapter 1 also describes which sample types are most useful for predicting postmortem interval based on the stage of decomposition, the knowledge gaps in the field, and the steps necessary for adoption of this tool into the justice system. During fresh and early decomposition, microbial succession of the skin and soil sample types are most predictive of postmortem interval. However, after approximately the first three weeks of decomposition, the changes in the microbial communities that are used for predictions begin to slow down and the skin and soil sample types become less useful for estimating postmortem interval. Chapter 2 of this dissertation shows that microbial succession of the bone microbial decomposer communities can be used for estimating postmortem interval during the advanced and skeletonization stages of decomposition. First, the bone microbial decomposer community was characterized using 16S ribosomal RNA sequencing from six human donor subjects placed in the spring and summer seasons at the Southeast Texas Applied Forensic Science Facility. A core bone decomposer microbiome dominated by taxa within phylum Proteobacteria was discovered, as well as significant overall differences in the bone microbial community between the spring and summer seasons. These microbial community data were used to develop random forest models that predicted postmortem interval within +/- 34 days over a 1–9-month time frame of decomposition. To gain a better understanding of where the microbes in the decomposed bone were coming from, as healthy, living bone is typically sterile, SourceTracker2 was used with paired skin and soil samples taken from the same decedents. Results showed that the bone microbial decomposer community is likely sourced from the surrounding environment, particularly the skin and soil communities that occur during the advanced stage of decomposition. Chapter 3 of this dissertation focuses on the influence of the blow fly (Calliphoridae) microbiome on human cadaver microbial community assembly. In early decomposition, volatiles attract blow flies to the cadaver, which serves as a source of nutrients and a safe place to lay eggs. It is likely that during this interaction between hosts, there is a mechanical transfer of microbes that subsequently alters each of their microbial communities. While studies have shown that blow flies have their own microbiome, they were not conducted in a decomposition environment. First, Chapter 3 shows the characterization of the blow fly microbiome by organ and season in a terrestrial, human decomposition environment. This was performed by placing ten cadavers across the winter, spring, and summer seasons at the Southeast Texas Applied Forensic Science Facility, collecting the first wave of colonizing flies for each cadaver, and sequencing the 16S ribosomal RNA gene of the labellum (mouth parts), tarsi (leg parts), and oocytes. Results showed that the previously defined universal fly microbiome persists even in a decomposition environment, with notable differences still present between organs and seasons. Additionally, results from using the tool SourceTracker2 showed that the labellum and tarsi act as substantial bacterial sources of the human decomposer bacterial community, and this source contribution varies by season. In summary, this dissertation provides the first quantitative estimate of postmortem interval of terrestrially decomposed human skeletal remains using microbial abundance information. This is a significant contribution to the criminal justice system; anthropologists typically use visual evidence to provide postmortem interval estimates of skeletal remains with errors ranging from months to years, whereas our approach provides estimates with errors of approximately one month. Furthermore, this dissertation shows evidence that there is a mechanical transfer of microbes between blow flies and human cadavers during the early stage of decomposition, which provides ecological insight into human cadaver microbial community assembly.